Pentagon fraud perspective analysis in detecting indications of financial statement fraud - Ayuningtyas, Ni Putu Winda; Sudana, I Putu; Suartana, I Wayan; Mimba, Ni Putu Sri Harta (International research journal of management, IT and social sciences, 2021)
This study aims to obtain empirical evidence regarding the elements of fraud pentagon theory on indications of financial statement fraud. This research was conducted on banking companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2020 period. The method of determining the sample used is non-probability sampling with purposive sampling technique. The number of samples that meet the sample selection criteria are 140 samples, namely 35 banking companies during the four years of observation 2017-2020. The data analysis technique used is multiple linear regression. Based on the results of the analysis, it is stated that the nature of industry and change of directors have a negative effect on indications of financial statement fraud, while personal financial need, rationalization, and CEO duality have no effect on indications of financial statement fraud. This study has implications for investors, creditors, the government and other parties who need financial statement information to consider the elements of the fraud pentagon theory to detect indications of fraudulent financial statements in banking companies.